Achieving sustainable urban mobility with a modified VIKOR method to improve the selection of a park and ride system - Muñoz-Medina, Belén; Ordoñez, Javier; Romana, Manuel G.; Alcaraz Carrillo de Albornoz, Vicente (Journal of Civil Engineering and Management, 2025)
In many European cities, municipal authorities have placed restrictions on private transport in city centres to comply with national and European regulations aimed at reducing traffic congestion, air pollution levels, polluting gases emission from transport and the consequences on climate change that have affected the quality of life of the inhabitants. Park and ride (P&R) facilities are key elements to introduce restrictions on private transport in city centres to reduce congestion. In this paper, a methodology is proposed, through multi-criteria decision methods, to determine a sustainable P&R rating and classification. The optimal solution or set of solutions, for P&R facilities is determined by taking into account sustainability criteria: environmental, economic, functional and social. A modified VIKOR multi-criteria decision method was developed and applied by using the Mahalanobis distance by taking into account the correlation between variables. The proposed methodology provides the most sustainable alternatives of P&R and allows local authorities to prioritize necessary actions to achieve more sustainable urban mobility. The method developed was applied to study the P&R system designed for the city of Madrid.